Czesław Miłosz „o sobie samym jako (o) innym”: Miłosz - Ricoeur - Rydz, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The article is thematically related to the fundamental essay by the French hermeneutic philosopher, On Oneself as Another, which discussed with reference to Miłosz’s later writings (poetry and essays). The autobiographical quality of Miłosz’s expression is discussed through the concept of “otherness” as presented by Ricoeur. The discussion is conducted in the framework of triple relation of a subjective “I”: to one’s body, to the Other, and to one’s conscience. Miłosz, in his later works, responds to the ailings of the body with understanding, or even a sort of tenderness. Similar emotions are evoked by his contact with the Other, embodied by his ancestors and contemporaries. The responsibility for another person, however, and the communion with fellow people, are related, in his work, with the category of conscience. An attempt to narrate “oneself as another” allowed the Polish poet to reduce the seemingly irremovable rift between an artist and “the human family”; that rift was for Miłosz a troublesome legacy of modernism.